Predicting and managing sepsis in burn patients: current perspectives - Nunez Lopez O; Cambiaso-Daniel J; Branski LK; Norbury WB; Herndon DN (Dove Medical Press, 2017)
Omar Nunez Lopez,1,2 Janos Cambiaso-Daniel,1–3 Ludwik K Branski,1,2 William B Norbury,1,2 David N Herndon1,2,4 1Department of Surgery, University of Texas Medical Branch, 2Shriners Hospitals for Children, Galveston, TX, USA; 3Division of Plastic, Aesthetic and Reconstructive Surgery, Department of Surgery, Medical University of Graz, Graz, Austria; 4Department of Pediatrics, University of Texas Medical Branch, Galveston, TX, USA Abstract: Modern burn care has led to unprecedented survival rates in burn patients whose injuries were fatal a few decades ago. Along with improved survival, new challenges have emerged in the management of burn patients. Infections top the list of the most common complication after burns, and sepsis is the leading cause of death in both adult and pediatric burn patients. The diagnosis and management of sepsis in burns is complex as a tremendous hypermetabolic response secondary to burn injury can be superimposed on systemic infection, leading to organ dysfunction. The management of a septic burn patient represents a challenging scenario that is commonly encountered by providers caring for burn patients despite preventive efforts. Here, we discuss the current perspectives in the diagnosis and treatment of sepsis and septic shock in burn patients. Keywords: burn injury, thermal injury, burn sepsis, procalcitonin, antibiotics, biomarkers, cytokines